SERUM ACTIVITY OF ANGIOTENSIN CONVERTING ENZYME AND BLOOD PRESSURE RESPONSE TO ACUTE DYNAMIC EXERCISE - Nakas-Icindic, Emina (Bosn J Basic Med Sci, 2004)
Angiotensin converting enzyme (ACE) plays an important role in blood pressure regulation not only in the state of rest, but also during physical exercise. The aim of this study was to estimate the serum ACE activity in response to acute dynamic exercise. The study involved a group of young, healthy, male volunteers (average 22 years of age). Exercise testing was carried out on ergometer bicycle according to the protocol of individually adjusted continuous, constant workload (3W/kg). The activity of ACE in serum was measured in venous blood, in the period of rest, in 4th, 8th and 12th minute of exercise and 1st, 3rd and 6th minute of recovery by spectrophotometric method. Marked inter-individual differences in basal serum ACE activity were determined (range 8, 31 - 63, 72 U/L). Serum ACE activity did not significantly vary during exercise and in the period of recovery. Systolic blood pressure changed during exercise compared to values during rest period in accordance with the applied type of dynamical exercise. Diastolic blood pressure did not vary considerably during exercise. Statistically significant correlation between mean arterial blood pressure and ACE activity in the serum was not found. The lack of increase of ACE activity in the serum, in spite of changes in blood pressure values, most likely shows the presence of alternative ACE independent pathway involved in the production of vasoactive substances that have important role in the regulation of cardiovascular system response to acute dynamic exercise.